2011
DOI: 10.1021/es2002327
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Silver Nanoparticles in Geochemically Heterogeneous Porous Media: Predicting Affinity from Surface Composition Analysis

Abstract: This study focused on the effect of surface heterogeneity on the affinity of nanoparticle (for that surface) and the viability of using surface composition analysis to facilitate the prediction of such an affinity. The transport of the uncoated silver nanoparticles (AgNPs) in a porous medium composed of silica glass beads partially covered with iron oxide was studied and compared to that in a porous medium composed of unmodified glass beads (GB). It was found that at relative high pH (8.3) there existed only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 119 publications
8
61
0
Order By: Relevance
“…The XRD spectra of AgNPs confirmed the metallic composition (Supporting Information, Figure S3a). A UV-Vis absorption spectrophotometer was used to estimate the AgNP concentration using the SPR peak of AgNPs that was observed at 395 nm in good agreement with the literature (Lin et al 2011) and our recent report (Dorney et al 2014). The absorbance of AgNPs increased after the addition of 10 mg L -1 of NOM, and further addition of NOM (40, 80 and 160 mg L -1 ) decreased the AgNP absorbance.…”
Section: Characterization Of Agnpssupporting
confidence: 79%
See 1 more Smart Citation
“…The XRD spectra of AgNPs confirmed the metallic composition (Supporting Information, Figure S3a). A UV-Vis absorption spectrophotometer was used to estimate the AgNP concentration using the SPR peak of AgNPs that was observed at 395 nm in good agreement with the literature (Lin et al 2011) and our recent report (Dorney et al 2014). The absorbance of AgNPs increased after the addition of 10 mg L -1 of NOM, and further addition of NOM (40, 80 and 160 mg L -1 ) decreased the AgNP absorbance.…”
Section: Characterization Of Agnpssupporting
confidence: 79%
“…A number of recent studies have examined the transport of unmodified and surface-modified AgNPs in saturated porous media (e.g., unmodified AgNPs (Lin et al 2011), citrate-stabilized AgNPs (El Badawy 2011Sagee et al 2012;Taghavy et al 2013), polyvinylpyrrolidone (PVP)-AgNPs Flory et al 2013;Lin et al 2012b;Mitzel and Tufenkji 2014;Sagee et al 2012;Song et al 2011), Gum Arabic-AgNPs (Lin et al 2012a;Song et al 2011), branched polyethyleneimine-coated AgNPs (El Badawy 2011), and proteinate-AgNPs (Ren and Smith 2013). These studies have reported the effect of flow velocity, pH, and ionic strength on AgNP transport.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, physico-chemical properties of soil and nanoparticles such as size, shape and surface charge are believed to exert important control on dissolution, agglomeration and aggregation of nanoparticles. Interestingly, enhanced ionic strength and divalent cations are reported to promote silver nanoparticle aggregation and retention in soil (Lin et al 2011 ;Thio et al 2012 ). Cornelis et al ( 2013 ) have suggested that heteroaggregation of silver nanoparticles with natural soil colloids signifi cantly reduce their mobility.…”
Section: Nanoparticle-soil Interactionsmentioning
confidence: 99%
“…According to the particle filtration theory, retention and mobility of NPs in porous media are controlled by physicochemical properties of both NPs and collector surfaces, such as the grain size (texture), input concentration, mineralogical composition, the presence of humic acid, the type of coatings or stabilizing agents, the solution chemistry, as well as by hydrodynamic forces (Lin et al, 2011;Liang et al, 2013a,b;Braun et al, 2015). The filtration theory has commonly been employed to describe the deposition of NPs on porous media surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies with NPs and natural colloids often showed deviations in predictions from filtration theory. For example, the retention of NPs may occur even under unfavorable conditions for attachment due to local surface charge heterogeneities (Lin et al, 2011), aggregation (Bradford et al, 2006), and straining in small pores and at locations of high surface roughness (Kasel et al, 2013a). Additionally, an increase in the NPs transport due to stabilizing agents causing short-range repulsive forces (El Badawy et al, 2013), retarded and asymmetric BTCs, and uniform, non-monotonic, and hyperexponential retention profiles (RPs) (Liang et al, 2013a) are examples of violations of the filtration theory.…”
Section: Introductionmentioning
confidence: 99%